A Multimodal Discourse Analysis in Media - Luca Ion-Sorin (Romanian Journal of English Studies, 2020)
This study attempts a multimodal discourse analysis of a newspaper article during the Brexit campaign. The aim is to help the audience decode and evaluate photographs and texts from media by providing a few strategies as guidance. The approach adopted for this analytical research is inspired by Halliday and Matthiessen’s An Introduction to Functional Grammar (2004). Consequently, the objects in a photograph and words in a text function similarly conveying information to the audience, and additionally, involve a similar strategy of analysis. To sum up, these strategies are intended to improve the audience’s comprehension of decoding article meaning and journalist’s intention.